MOLECULAR CLONING AND ANALYSIS OF A CONSTANS HOMOLOG FROM NICOTIANA TABACUM - Y. Lu; Y. Liu; Y. Sun; J. Mu; M. Ren; X. Zhang; Z. Wang The Graduate School of Chinese Academy of Agricultural Sciences; Beijing; P.R. China (Journal of Animal and Plant Sciences, 2013)
Plant development is largely controlled by day length. In Arabidopsis thaliana, the CONSTANS (CO) gene plays a pivotal role in the photoperiodic pathway controlling floral transition. In this research, we employed Nicotiana tabacum cv. Kutsaga Mammoth 10 as experimental materials and designed hetrologous primers based on the S. tuberosum CO gene sequence and tobacco expressed sequence tags (ESTs). By using the approach of RT–PCR combined with rapid amplification of cDNA ends (RACE) technology, a novel cDNA encoding a CO homolog named NtCO1 (GenBank accession number, JN022535.1) was cloned. The full-length cDNA sequence isolated was 1493 bp with an open reading frame (ORF) of 1211 bp, encoding a protein of 403 amino acids. The predicted NtCO1 protein contains two B-box-type zinc fingers and a CCT domain. Analysis based on amino acid sequence alignment showed that NtCO1 shares high identity with StCO (86.5%) from Solanum tuberosum , AtCO (50%) from A. thaliana and Hd1 (43.7%) from Oryza sativa. Semi-quantitative RT–PCR analysis showed that NtCO1 was expressed specifically and strongly in leaf tissues but weakly in stem and root tissues.
Keywords: CONSTANS (CO) gene; tobacco; cloning; analysis; NtCO1